Cryosphere melt over the Third Pole - Tandong YAO; Lonnie THOMPSON; Wusheng YU; Wei YANG; Yang GAO (Zenodo, 2020)
This repository includes the datasetassociated to the following paper submittedtoNature 2020: Tandong Yao, Lonnie Thompson, Wusheng Yu, et al., Cryosphere melt and its role to water balance over the Third Pole. Figure 1. The GMWE variations based on the in-situ measurements in the endorheic and exorheic zones over the TP during 2000–2018 Figure 2. The PMWE variations based on the in-situ measurements in the endorheic and exorheic zones over the TP during 2000–2018 Figure 3. The SMWE variations based on the in-situ measurements in the endorheic and exorheic zones over the TP during 2000–2018 Figure 4. Spatiotemporal variations of cryosphere melt and its linkage with water storage in the endorheic and exorheic zones over the TP during 2000–2018 Figure S7. Temporal changes of glacier melt water equivalent (GMWE) Figure S8. Annual glacier melt water equivalent (GMWE) from 2000 to 2018 over the TP Figure S9. Temporal changes of Permafrost melt water equivalent (PMWE) in the endorheic and exorheic zones Figure S10. PMWE changes in different time spans over the TP Figure S11. Temporal changes of snow melt water equivalent (SMWE) Figure S12. Annual snow melt water equivalent (SMWE) from 2000 to 2018 in the TP Figure S13.The average GMWE, PMWE and SMWE in each basin over the TP Figure S14. Annual variations of cryosphere melt in the endorheic and exorheic zones over the TP